Mergers and acquisitions in the banking sector of the Republic of Serbia - Stefanović, Dragana; Vapa Tankosić, Jelena; Mirjanić, Borjana (Pravo, teorija i praksa, 2025)
As a form of foreign direct investment, mergers and acquisitions have become an important form of cross-border investment in developing and transition countries since the last century. For a country to attract such investments, it must meet specific conditions, including political stability and favorable macroeconomic indicators. Following a period of political instability and economic crisis, Serbia has once again become an attractive destination for foreign investments, including mergers and acquisitions. This paper uses a qualitative methodology to analyze the trends and value of mergers and acquisitions in Serbia in the 21st century, with a particular focus on the banking sector. The aim of the paper is to show how mergers and acquisitions have shaped the banking sector in Serbia and to identify the key factors that have influenced these processes.